A new approach for second‐order perturbation theory. Issue 14 (4th March 2016) - Tomlinson, David G.; Asadchev, Andrey; Gordon, Mark S.
Abstract : A new second‐order perturbation theory (MP2) approach is presented for closed shell energy evaluations. The new algorithm has a significantly lower memory footprint, a lower FLOP (floating point operations) count, and a lower time to solution compared to previously implemented parallel MP2 methods in the GAMESS software package. Additionally, this algorithm features an adaptive approach for the disk/distributed memory storage of the MP2 amplitudes. The algorithm works well on a single workstation, small cluster, and large Cray cluster, and it allows one to perform large calculations with thousands of basis functions in a matter of hours on a single workstation. The same algorithm has been adapted for graphical processing unit (GPU) architecture. The performance of the new GPU algorithm is also discussed. © 2016 Wiley Periodicals, Inc. Abstract : The two main ways data can be stored during a quantum chemistry calculation are in main memory or on the disk. Storing data in memory for the duration of a run is preferred, if the amount of data is small enough to fit in memory. A new approach to MP2 is presented that can use either memory or disk, depending on the problem size.